Immunity Enhancement in Immunocompromised Gastrointestinal Cancer Patients with Allogeneic Umbilical Cord Blood Mononuclear Cell Transfusion. (26th April 2017) - Qiu, Ying; Zhao, Ruidong; Yun, Mark M.; Han, Xia; Yun, Feiyu; Liu, Bingchun; Zhou, Erxia; Ouyang, Xiaohui; Yun, Sheng
Abstract : Objectives . In order to enhance the immunity of cancer patients to prevent relapse or to prolong survival time, umbilical cord blood mononuclear cells (UCMCs) were transplanted to cancer patients. Patients and Methods . UCMCs were transfused to 63 immunocompromised gastrointestinal cancer patients with nonmyeloablative (NMA) conditioning regimen. Results . The clinical study showed that the number of both T and B cells increased much more rapidly after transfusion of UCMCs than that of the control group without transplantation (p < 0.01 ). Proinflammation cytokines IFN γ and TNF α in serum increased to or above the normal range in 80.9% of patients at 12 weeks after UCMC transfusion. However, they recovered to the normal range in 21.7% of patients at the same time point in the control group only. In addition, the clinical investigation also showed that the transfusion of UCMC increased stable disease (SD) and reduced progressive disease (PD) significantly (p < 0.01 ); however, it did not have significant effects on complete response (CR), partial response (PR), or mortality rates compared with the control group (p > 0.05 ). Conclusions . UCMCs have powerful repairing effects on damaged cells and tissues and may reconstruct the impaired immunity. Transfusion of UCMCs could reconstruct the immunity of cancer patients with immunosuppression.